2017
DOI: 10.1002/14651858.cd005186.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to improve hand hygiene compliance in patient care

Abstract: Background Health care-associated infection is a major cause of morbidity and mortality. Hand hygiene is regarded as an e ective preventive measure. This is an update of a previously published review. Objectives To assess the short-and long-term success of strategies to improve compliance to recommendations for hand hygiene, and to determine whether an increase in hand hygiene compliance can reduce rates of health care-associated infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
170
0
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 322 publications
(204 citation statements)
references
References 128 publications
3
170
0
13
Order By: Relevance
“…2 However, achieving significant and sustained improvement has been challenging. 3 Hand hygiene is increasingly recognized as a complex behaviour with numerous motivators and barriers. 2 Researchers have begun to focus on applying behavioural psychology to bring about improvement.…”
Section: Introductionmentioning
confidence: 99%
“…2 However, achieving significant and sustained improvement has been challenging. 3 Hand hygiene is increasingly recognized as a complex behaviour with numerous motivators and barriers. 2 Researchers have begun to focus on applying behavioural psychology to bring about improvement.…”
Section: Introductionmentioning
confidence: 99%
“…12 No intervention studies with explicit reference to psychological theories had been published until April 2011, 13 and recent trials have been limited to nurses 14,15 or are still underway. 16,17 Exploratory studies have tended to consider hand hygiene behaviour (HHB) as reasoned actions directly influenced by behavioural intentions.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Improvement of health care workers' hand hygiene practices is therefore a challenge, and multiple studies have indicated that hand hygiene compliance can only be improved and sustained through the use of an approach that takes into account the multifaceted nature of behavior change. [8][9][10] Efforts to improve hand hygiene compliance include continuous education and motivation programs [9][10][11][12] and measurement and feedback of hand hygiene compliance rate to users. 2,9,10,12 One important factor known to influence hand hygiene performance is the availability, utility, and accessibility of hand hygiene products.…”
mentioning
confidence: 99%
“…[8][9][10] Efforts to improve hand hygiene compliance include continuous education and motivation programs [9][10][11][12] and measurement and feedback of hand hygiene compliance rate to users. 2,9,10,12 One important factor known to influence hand hygiene performance is the availability, utility, and accessibility of hand hygiene products. 2 Evidence and best practice indicates that in some instances of hand hygiene practice, the location and accessibility of hand hygiene products directly influence hand hygiene behavior.…”
mentioning
confidence: 99%
See 1 more Smart Citation